Cooperation in innovation networks: The case of Danish and German SMEs - Susanne Gretzinger; Holger Hinz; Wenzel Matiaske (Management Revue, 2010)
Information is a critical resource in innovation processes. External information can be helpful in innovation processes to complete them successfully. SMEs in particular are therefore advised to draw on consulting in innovation processes, as they cannot ensure the necessary information flow internally due to the lesser resources they have compared to larger companies. To promote economically relevant information of SMEs, the public sector provides specific advisory services. These services, however, are rarely utilized compared to direct customer and supplier contacts. From strategic management's point of view, the involvement of intermediaries in the innovation process is accompanied by the risk of losing specific knowledge to the business environment. Based on an empirical comparative study of Danish and German SMEs - Danish companies utilize public as well as private consulting services more often - determinants of the usage of business consultancies in innovation processes are elicited.
Keywords: 650; SMEs; innovation; networks; public policy